High speed UX : bridging design and performance (O'Reilly, 2015)
"Which would you rather have: A rich design or a fast user experience? Users want both, but sometimes the interplay between design and performance feels like one side's gain is the other side's loss. Design and performance are indeed connected, but they aren't opposing forces. Instead, they complement each other. The trick for us as designers and developers is figuring out how to make it work. In this video presentation, Steve Souders, former Chief Performance Yahoo! and Google head performance engineer, explains a process that brings design and performance together at the beginning of a project to deliver a web experience that's both fast and rich. Learn how to place emphasis on early prototyping and tracking performance from the get-go. Developers will benefit by participating in the product definition process, while designers will benefit from understanding more about how designs are implemented. You'll also discover new metrics that focus on what a user actually sees as the page loads. With this video, you'll learn how to bridge the technical and language gaps that, so far, have hindered the seamless creation of great user experiences."--Resource description page.